Necrotizing pneumonia in children: 10 years of experience in a Pediatric Reference Hospital (Archives of Pediatrics of Uruguay, 2020)
Introduction: necrotizing pneumonia (NP) is a complication of community-acquired pneumonia (CAP) in hospitalized children, with significantly high morbidity. A case definition was devised in 2009, which enabled physicians to unify criteria and rationalize resources for the assistance of children with NP.Objective: describe clinical characteristics and evolution of children who developed NP.Methodology: descriptive study, NP hospitalized children between 1/1/2009 and 12/31/2018. Case definition: pneumatoceles and one or more of the following criteria: malaise, persistent/recurrent fever, white blood cell count over 30,000 or less than 5.000/mm3, C-reactive protein over 120 mg/dL, lactic dehydrogenase in pleural fluid over 2,500UI/L and/or bronchopleural fistula (BPF). Clinical, epidemiological, etiological and evolutionary characteristics were described.Results: NP was diagnosed in 197 children (7.92% of CAP hospitalizations), with variable annual cases and annual rate/10,000 discharges. Children had a median age of 25 months; 89.8% were previously healthy. They presented fever prior to diagnosis, median 5 days, multilobar pneumonia 58%, respiratory failure 62%, sepsis 19%, empyema 80% and BPF 51%, persistent fever median 7 days. 46% required intensive care and 18% required assisted mechanical ventilation. Acute phase reactants on admission were high. An etiological agent was identified in 102 cases, S.pneumoniae in 92. Two children died.Conclusions: NP was a frequent complication in CAP hospitalized children. Clinical presentation and evolution were severe. The etiological identification was high, most of them corresponded to S. pnuemoniae. Mortality was low.
Keywords: Necrotizing pneumonia; Pneumococcal pneumonia; Community-acquired infections; Child